OLIGOCENE – EARLY MIOCENE (MAYKOP) DEPOSITS IN KARKINITE NORTH-CRIMEAN SEDIMENTARY BASIN: GEOLOGICAL AND PALEO-OCEANOGRAPHIC SEDIMENTATION SETTING - Grygorchuk, K.; Gnidets, V.; Kokhan, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The paper deals with featuring lithology of the Oligocene-Early Miocene sedimentary complex within the Karkinite North-Crimean basin and reconstructing its sedimentation setting. The research involves lithological, facial, litmological, sedimentary, and paleo-oceanographic analyses. It is established that lithological structure of the Maykop series in its section is represented by interstratifications of clay, silt, and psammitic lithological rocks, which are grouped in aleuritic-sandstone litmites, clayish litmites, and mixed ones; the latter equally containing mudstones, siltstones, and sandstones. Subregionally distributed clastogenic litmites reveal cases of massive regressive sedimentation and act as stratigraphic marks. The major sand-aleuritic accumulations are found to be bars, barrier islands, and alluvial fans. The paper makes the first attempt to reconstruct sedimentary and paleo-oceanographic setting for Oligocene-Early Miocene clastogenic sedimentation within the north-western shelf of the Black Sea and the adjacent landmass. Besides, it provides sedimentation models for heterochronous rock intervals and determines the nature of spatiotemporal distribution of heterogeneous bodies. Studying lithology of strata and creating sedimentation models will promote an insight into stratigraphy and spatio-chronological distribution of heterogeneous sedimentary rocks, in particular. This will lay lithogenetic basis for accurate forecasting prospective oil and gas-bearing rocks and their spatio-chronological distribution.